Rancang Bangun Aplikasi Mobile Learning Tuntunan Shalat - Jodi Hendrawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The development of information technology is currently growing rapidly and widely used in meeting human needs. However, the present presentation of information is still experiencing many obstacles in its less effective and inefficient presentation, such as information on worship, wudhu and adzan especially for Muslims which still must be obtained from religious figures, print media, magazines and books which is less effective and inefficient because it must provide a special time, a certain place and spend the cost to get the information. These problems can be overcome by utilizing the development of information technology that is the learning media (M-Learning) on ​​Andoid mobile devices. The design of the application can use object-oriented design tools with UML modeling (Unified Modeling Language) which is dominated by objects and denoted in specific symbols. With the application of mobile learning on mobile devices, the presentation of information about prayer, wudhu and adzan for Muslims becomes more effective, accessible anywhere, anytime, and the delivery of information becomes more interactive. Keywords :Android, Learning, UML, Shalat